Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
20th AIAA/CEAS Aeroacoustics Conference 2014
DOI: 10.2514/6.2014-3102
|View full text |Cite
|
Sign up to set email alerts
|

Turbofan Inlet Distortion Noise Prediction with a Hybrid CFD-CAA Approach

Abstract: Modern turbofan engines have drooped inlets which cause the mean flow into the fan to be circumferentially non-uniform at practically all flight conditions. This effect leads to the appearance of additional fan noise sources which propagate even at subsonic rotor tip speeds. In this paper we demonstrate a hybrid CFD-CAA methodology for predicting fan inlet noise in the presence of such distorted mean flows. A compressible URANS simulation is performed to first capture the unsteady acoustic source terms, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 12 publications
0
12
0
Order By: Relevance
“…Holewa et al studied the effect of the bifurcations on fan noise [38]. Winkler et al considered the effect of an inlet distortion on short engine inlets [39]. But only recently Daroukh et al considered all the effects together by computing the 360 • of a typical UHBR turbofan including a short nacelle, a strong OGV heterogeneity and the IGV of the primary engine stream, both at approach [11] and cutback conditions [40].…”
Section: Resultsmentioning
confidence: 99%
“…Holewa et al studied the effect of the bifurcations on fan noise [38]. Winkler et al considered the effect of an inlet distortion on short engine inlets [39]. But only recently Daroukh et al considered all the effects together by computing the 360 • of a typical UHBR turbofan including a short nacelle, a strong OGV heterogeneity and the IGV of the primary engine stream, both at approach [11] and cutback conditions [40].…”
Section: Resultsmentioning
confidence: 99%
“…This heterogeneity of the entering flow in short intakes is amplified at OP (Operating Point) conditions with non-zero AoA (Angle of Attack), typically for AoA = 10-15° for which the inflow direction is not aligned with the axis of the nacelle. As shown by recent studies [1] [2] [3][4] [5], such inflow distortions can highly modify the tone noise characteristics known from conventional turbofans. This paper presents aeroacoustic investigations performed by ONERA on a full-scale UHBR engine in the framework of the CleanSky2 European project, ASPIRE, in collaboration with NLR, DLR, and Airbus.…”
Section: Introductionmentioning
confidence: 99%
“…This is typically the case during landing or take-off operations (angle of attack around 10°-15°) where airport neighbours are the most exposed to noise nuisance. Several recent studies have therefore focused on the impact of distortion on the noise emitted by turbofan engines [1][2][3][4][5][6][7][8]. They have shown that the tone noise characteristics can be significantly modified by: (a) introducing new acoustic sources caused by the distortion/fan blades interaction [3][4][5], (b) modifying the conventional fan-blade wakes/Outlet Guide Vanes (OGVs) interaction [3][4][5]8], and (c) modifying the generation and propagation of fan-blade shocks at transonic speeds [1][2][3][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…However, the associated computational cost is very high and the radiation of acoustic waves outside of the nacelle cannot be correctly captured over an important distance. Most of the studies [1,3,7] are therefore based on a two-step methodology where the CFD solution is chained to a Computational AeroAcoustics (CAA) solver to propagate and radiate the shocks. The latter methodology is chosen here using the CFD/CAA chaining strategy developed by Thisse et al [9,10].…”
Section: Introductionmentioning
confidence: 99%